Regional pathways to complexity : settlement and land-use dynamics in early Italy from the Bronze Age to the Republican period - Attema, P. A. J. (Amsterdam archaeological studies ;, 2010)
Synthesizing almost 30 years of Dutch archaeological research in central and southern Italy, this book discusses and compares settlement and land use patterns from the late protohistoric period to the late Roman Republic. Exploring both social and environmental explanations, as well as interregional parallellisms and divergences, the authors take a multi-scalar approach (from micro-regional to supra-regional) to the long-term development of Indigenous Bronze Age tribal pastoralist societies towards the complexity of urbanized Roman society. The culmination of a joint project conducted between.